Bridging Culture and Technology: Integrating Minangkabau Ethnomathematics into Virtual Reality for Geometry Learning - Zulfa Amrina; Joni Alfino; Syafni Gustina Sari; Ade Sri Madona; Nurham Hahsa (FKIP Universitas Lampung, 2026)
This research is based on the fact that younger generations have difficulty understanding mathematics and are also less culturally aware. Observing this phenomenon, it is necessary to develop a culture-based (ethnomathematics) learning media. The purpose of this study is to develop an ethnomathematics-based mathematics learning media by exploring the Minangkabau Rumah Gadang (traditional house) through virtual reality technology. The research method used in this study was research and development (R&D), which followed the ADDIE model, which consists of five phases: analyze, design, develop, implement, and evaluate. The media was developed using the Artsteps application. The media developed was validated by experts before being tested on students as research subjects. Data were collected from two material-expert lecturers and one media-expert lecturer, as well as from one class of 44 students, serving as the product trial sample. The instruments used in this study were the material expert validation sheet, the media expert validation sheet, the student response questionnaire, and the mathematics learning achievement test. The results of this study showed that the material expert gave a score of 98%, the media expert 97%, and the practitioners (student responses) 98%, with an average score of 97.7%, which falls into the “excellent” category. Meanwhile, the mathematics learning achievement test showed that 84.1% of the students met the passing criteria in this course, while 15.9% failed. Based on the research results and discussion, it can be concluded that the Minangkabau culture-based ethnomathematics learning media developed through the ADDIE model meets the criteria for validity and practicality for implementation with Elementary School Teacher Education students. Keywords: ethnomathematics, virtual reality, mathematics, learning_media.